Respuesta :

4x(x-2)=(2x+1)(2x-3)
in the first expression distribute the 4x, in the second expression FOIL

4x²-8x=4x²-6x+2x-3
combine like terms

4x²-8x=4x²-4x-3
subtract 4x² from each side 

-8x=-4x-3
add 8x to each side 

0=4x-3
add 3 to each side 

3=4x
divide by 4 on each side 

x= 3/4 or 0.75
4x(x-2) = (2x+1) (2x-3)
Distributive property: 4x^2 - 8x = 4x^2 - 6x + 2x -3
subtract 4x^2 both side : -8x=-4x-3
                                         +4x      +4x
                                         -4x=-3
x= 3/4